Dual limit analysis problems with discontinuity of displacement velocities - Kalanta, S. (Journal of Civil Engineering and Management, 1995)
The general dual mathematical models (static and kinematic formulations) of the limit load and rigidplastic body parameters optimization problems are formed on the basis of extremal energy principles and theory of duality. Yield conditions are controlled not only in volume of finite elements, but also at the surfaces between elements. Therefore the possible discontinuity of displacement velocities and velocity energy dissipation between the elements are evaluated.Article in Russian.Dualūs ridinės pusiausvyros uždaviniai su poslinkių greičių trūkiaisSantrauka. Sudarytos standaus—plastinio kūno parametrų ir ribinės apkrovos optimizacijos uždavinių dualūs matematiniai modeliai statinėje ir kinematinėje formuluotėje. Juose takumo sąlygos tikrinamos ne tik baigtinių elementų tūryje, bet ir jų paviršiuose. To pasekoje dualiose formuluotėse įvertinami galimi poslinkių greičių trūkiai ir energijos disipacijos greitis paviršiuose tarp elementų.First Published Online: 26 Jul 2012